Penerapan Aplikasi Quizizz dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam Siswa Kelas VIII SMP Negeri 4 Bontang Barat Tahun Pelajaran 2023/2024 - Angzalni, Aliyah; Aslam, Aslam (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to evaluate the effectiveness of the Quizizz application in improving the academic performance of Grade VIII Islamic Education (PAI) students at SMP Negeri 4 Bontang Barat in the 2023/2024 academic year. The research employs an experimental method with 15 Muslim students as subjects. The learning process was conducted by integrating the Quizizz application as an evaluation and interactive learning tool. Data collection was done through written tests before and after using the Quizizz application, as well as several direct observation activities during the learning process. The results of the study indicate a significant improvement in students' academic performance after using Quizizz. Student scores increased from the lowest score of 55 in the initial test to 70 for the lowest score in the final test. Additionally, observations during the learning process revealed that students were more enthusiastic and motivated in participating in Islamic Education lessons due to the interactive features of Quizizz, which made learning more engaging and enjoyable. Recommendations are given to teachers to consider using the Quizizz application or similar applications in the learning process to enhance student motivation, interest in learning, academic performance, and student engagement. The study also suggests that further research be conducted with a larger sample and in other subjects to test the consistency of the results and to expand the understanding of the effectiveness of technology use in education. The conclusion of this study is that the application of Quizizz is quite effective in making students show high enthusiasm and actively respond to quizzes. The data shows a significant increase in students' average scores after using Quizizz.